Perivascular adipose tissue-dependent chemerin release: the role of statins and thromboxane - Alsahli, Tariq (2021)
Perivascular adipose tissue (PVAT) is the fat tissue that surrounds most systemic blood vessels. Owing to its’ unique anatomical location, PVAT can directly regulate vascular tone and other aspects of vascular function via its secretome. Chemerin is an adipokine secreted from liver and adipose tissue, including PVAT, and is implicated in blood pressure regulation, with well-established roles in inflammation and obesity. Despite the fact that PVAT and chemerin have emerged as promising drug targets for many diseases, including obesity and obesity-associated cardiovascular diseases, less is known about their interaction with current cardiovascular drugs. Considering the well-documented pleiotropic effects of statins, which are not related to statin’s ability to inhibit cholesterol biosynthesis, the principal aim of this study was to determine the possible effects of statins on PVAT’s regulation of porcine coronary arteries (PCAs). PVAT from porcine coronary caused a time-dependent contraction of PCAs at baseline tone and potentiated contraction in the presence of the thromboxane mimetic U46619 through Ca2+-dependent pathways. The lipophilic simvastatin, but not the hydrophilic pravastatin, caused a concentration-dependent inhibition of PVAT-induced contraction at baseline tone and in the presence of U46619. Simvastatin caused inhibition of PVAT-induced contraction through a direct effect on PCAs and on the release of vasocontractile chemerin from PVAT. Simvastatin consistently inhibited the basal release of total chemerin in a concentration-dependent manner from both porcine coronary PVAT and 3T3-L1 adipocytes through a mevalonate-independent pathway. Simvastatin also prevented enhanced chemerin release from 3T3-L1 adipocytes following incubation with lipopolysaccharide (LPS) or the KATP channels opener, pinacidil. Furthermore, 48 h, but not 24 h, treatment with the PPARγ agonist rosiglitazone stimulated the release of chemerin levels and reversed simvastatin-mediated inhibition of chemerin release from cultured 3T3-L1 adipocytes. Pre-contraction with U46619 enhanced chemerin-9-induced contraction of isolated PCA, and chemerin-9-induced contraction involved ERK, Rho kinase, and calcium influx, with a role for calcium influx, in particular, in the enhancement of the contraction by U46619. Clinically, there is evidence that statins produce beneficial effects, including anti-inflammatory effects and reduction in blood pressure unrelated to cholesterol lowering, and the present study suggests that reducing chemerin release may be, at least partially, behind this effect. This thesis demonstrated that the co-release of thromboxane and chemerin from PVAT may produce a synergistic effect on coronary arteries that enhances contractile responses. These findings may be important for the control of adipose tissue-induced vascular alterations in obesity and associated diseases.